Physical properties of human premolar cementum: hardness and elasticity - Chutimanutskul Wanjira; Ali Darendeliler M.; Swain Michael V.; Shen Gang; Petocz Peter (Sciendo, 2005)
Aims: To determine if the cementum on the maxillary right and left first premolars has identical physical properties.